Fuzzy approach to estimate the demand and supply quantitative imbalance at the labor market of information technology specialists - Jabrayilova, Zarifa; Mammadova, Masuma; Mammadzade, Faig (International Journal of Intelligent Systems and Applications in Engineering, 2015)
This document considers the processes of modelling supply and demand interactions in the labour market for information technology experts (IT professionals) and management of their quantitative disparity at the macro level. The types of supply and demand imbalance for IT professionals are marked out. The methods are proposed for estimating the structural mismatch in the labour market for IT professionals, the degree of supply and demand imbalance for IT professionals based on fuzzy unbalance scale. The algorithm of fuzzy classification of states of imbalance is proposed.This document considers the processes of modelling supply and demand interactions in the labour market for information technology experts (IT professionals) and management of their quantitative disparity at the macro level. The types of supply and demand imbalance for IT professionals are marked out. The methods are proposed for estimating the structural mismatch in the labour market for IT professionals, the degree of supply and demand imbalance for IT professionals based on fuzzy unbalance scale. The algorithm of fuzzy classification of states of imbalance is proposed.